MENHIR DI DAERAH DENATANA, KECAMATAN WOLOMEZE, KABUPATEN NGADA, NUSA TENGGARA TIMUR SEBAGAI OBJEK GEOWISATA UNTUK KUNJUNGAN DIKLAT GEOWISATA - Pudjo Asmoro; Fiati Nurmaya (PPSDM Geominerba, 2018)
There are at least three menhir locations in Ngada Regency, Flores, East Nusa Tenggara, such as menhir which is located in the middle of rice field in Mengeruda Village, Soa Subdistrict;menhir in Naru Village; and menhir in Tiwuriwu Village, Bena, Jerebuu Subdistrict. These menhirs are still oftenly used for traditional events. Menhir has become one of the interesting sites to visit. Aside from being an educational tourism object, menhir is also used as a research object or as an object of natural beauty. Menhirs formed by natural processes in the Denatana are only formed on the cliffs of the Nginamanu River and have relatively similar morphology and physical properties of rocks with other places. The menhir consists of pillars composed by pumice brecciaswhich is spread along the river valley. The menhir constituent rocks in the form of pyroclastic deposits are, laharic, compact, clastic, in a grain size up to 5 cm, with the main component of pumis. The erosion process producesa rock arrangement in the form of a menhir arrangement trending northwest-southeast. There were no former human activities or traditional ceremonies around the menhir. This study aims to collect data information of inventory data on menhir geotourism objects in Ngada Regency and its surroundings which is expected to provide alternative locations for the Field Practice of environmental geology training, especially Geotourism Geology training. The results showed that the menhirs found in the Denatana area, Wolomeze Subdistrict were formed on pumice breccia rocks on the cliffs of the Nginamanu River with a slope of 30o -40o for the southern cliff and between 60o-80o for the northern cliffs, in the shape of thick and thin pillars, due to the erosion process upstream and to the sideways.